Big Data and Dahl's Challenge of Democratic Governance. - Ingrams, Alex (Review of Policy Research, 2019)
Big data applications have been acclaimed as potentially transformative for the public sector. But, despite this acclaim, most theory of big data is narrowly focused around technocratic goals. The conceptual frameworks that situate big data within democratic governance systems recognizing the role of citizens are still missing. This paper explores the democratic governance impacts of big data in three policy areas using Robert Dahl's dimensions of control and autonomy. Key impacts and potential tensions are highlighted. There is evidence of impacts on both dimensions, but the dimensions conflict as well as align in notable ways and focused policy efforts will be needed to find a balance.